Mixed Convection Heat and Mass Transfer in a Micropolar Fluid with Soret and Dufour Effects (Advances in Applied Mathematics and Mechanics, 2011)
A mathematical model for the steady, mixed convection heat and mass transfer along a semi-infinite vertical plate embedded in a micropolar fluid in the presence of Soret and Dufour effects is presented. The non-linear governing equations and their associated boundary conditionsare initially cast into dimensionless forms using local similaritytransformations. The resulting system of equations is then solvednumerically using the Keller-box method. The numerical results arecompared and found to be in good agreement with previously publishedresults as special cases of the present investigation. The non-dimensionalvelocity, microrotation, temperature and concentration profiles aredisplayed graphically for different values of coupling number, Soretand Dufour numbers. In addition, the skin-friction coefficient, theNusselt number and Sherwood number are shown in a tabular form.